The Influence of Religiosity, Motivation, Commitment, and Leadership Style on the Performance of Management (A Study on the Santri Organization at PPTQ Daarul Fath Pengging Boyolali) - Yunianto, Tri Wahyu; Hendra TS, Kartika; Sudarwati (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2026)
The purpose of this research is to ascertain how much the religiosity, motivation, commitment, and leadership style factors affect the OSDA (Student Organization) management's performance at PPTQ Daarul Fath Pengging Boyolali, both jointly (simultaneously) and separately (partially). All of 56 OSDA's managements were included in this research as total or saturated sampling method, which employed a quantitative methodology. Questionnaires were used to gather information. Multiple linear regression, the F-test, the t-test, and the coefficient of determination (R2) were all used in the data analysis. According to this research, OSDA’s managements performance is significantly impacted by religiosity. In the meanwhile, motivation, commitment, and leadership style have no bearing. Based on these findings, the researcher suggests to OSDA's managements to improve performance in a sustainable way, and also continuously strengthens religious components while also creating adaptable motivation, commitment, and leadership style.